Pharmacotherapy of anxiety disorders: a critical review - Koen, Nastassja (Les Laboratoires Servier, 2011)
Given the enormous contribution of anxiety disorders to the burden of disease, it is key to optimize their prevention and treatment. In this critical review we assess advances in the pharmacotherapy of anxiety disorders, as well as remaining challenges, in recent decades, the field has seen rigorous clinical trial methods to quantify the efficacy and safety of serendipitously discovered agents, more focused development of medications with selective mechanisms of action, and the gradual translation of insights from laboratory research into proof-of-principle clinical trials. On the positive side, a considerable database of studies shows efficacy and relative tolerability of the selective serotonin reuptake inhibitors in the major anxiety disorders, and secondary analyses of such datasets have informed questions such as optimal definition of response and remission, optimal dose and duration, and comparative efficacy of different agents. Significant challenges in the field include barriers to appropriate diagnosis and treatment of anxiety disorders, failure of a significant proportion of patients to respond to first-line pharmacotherapy agents, and a limited database of efficacy or effectiveness studies to guide treatment in such cases.